2021
DOI: 10.1093/ecco-jcc/jjab076.528
|View full text |Cite
|
Sign up to set email alerts
|

P404 Healthcare utilization and expenditures for patients with Ulcerative Colitis on advanced therapies in Germany

Abstract: Background Ulcerative Colitis (UC) is a chronic inflammatory condition, which significantly impacts patients’ health-related quality of life and burdens healthcare budgets. Our objective was to provide an overview of the healthcare resource use (HCRU) for the treatment of moderate to severe UC in Germany. Methods A retrospective analysis was conducted using claims data from a German sickness fund (AOK PLUS). Patients were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Germany, Teich et al found that initiation of golimumab was associated with significant improvements ( P < 0.0001) in work productivity and the capacity for daily activities starting as early as month 3, with these improvements maintained up to 24 months (end of study follow-up) [ 39 ]. Picker et al also found that patients receiving anti-TNFs, vedolizumab, or tofacitinib who were previously treated with advanced therapies had fewer sick days from work than treatment-naïve patients (12.2 vs. 13.2) per year and lower costs associated with UC-related sick leave (€2909 vs. €3404 per patient-year) [ 81 , 82 ]. Cross et al found that patients in the USA who were treated with biologics or JAK inhibitors were burdened most by impaired daily activities due to UC, followed by loss of work productivity, work impairments, and work time missed.…”
Section: Resultsmentioning
confidence: 99%
“…In Germany, Teich et al found that initiation of golimumab was associated with significant improvements ( P < 0.0001) in work productivity and the capacity for daily activities starting as early as month 3, with these improvements maintained up to 24 months (end of study follow-up) [ 39 ]. Picker et al also found that patients receiving anti-TNFs, vedolizumab, or tofacitinib who were previously treated with advanced therapies had fewer sick days from work than treatment-naïve patients (12.2 vs. 13.2) per year and lower costs associated with UC-related sick leave (€2909 vs. €3404 per patient-year) [ 81 , 82 ]. Cross et al found that patients in the USA who were treated with biologics or JAK inhibitors were burdened most by impaired daily activities due to UC, followed by loss of work productivity, work impairments, and work time missed.…”
Section: Resultsmentioning
confidence: 99%